EFEKTIVITAS KOMUNIKASI “KABA PADANG PANJANG” PADA VIDEOTRON SEBAGAI MEDIA INFORMASI PEMERINTAHAN BAGI MASYARAKAT KOTA PADANG PANJANG - Odna Nofri Yanti; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Videotron is one of the outdoor advertising media that is used by the private companies to promote their product. But as time goes by, the government also use Videotron, like The Government of Padang Panjang. This study aims to know how is the communication Effectivity of "Kaba Padang Panjang" in Videotron as government's media to spread information to Padang Panjang citizen. This study use quantitative methods, with questionnaire as the data collection technique with 96 respondent based on Unknown Population formula. The sampling technique used in this study is accidental sampling. Data analysis technique in this study used descriptive statistic. The result in this study shows that “Kaba Padang Panjang” in Videotron's effective as information media to Padang Panjang citizen. It is known from data processing based on six indicators and variable of communication effectivity by Hardjana. Every indicator have different scale. 2,64 for receiver indicator, 3, 14 for message content indicator, 2,40 for timing indicator, 2,76 for media indicator, 3,8 for format indicator, 2,45 for source indicator. The highest scale are in format indicator and the lowest scale is in timing indicator. The result is based on average formula of all indicators which is 2,76 and it is in effective scale. It is shown that “Kaba Padang Panjang” is effective as government's information media to Padang Panjang citizen.  Key Word : Communication Effectivity, Videotron, Information, Citizen